(untitled) (Contemporary Mathematics, 2025)
In the present study, we develop a well-behaved null tetrad for the exterior Schwarzschild metric. Additionally, under certain conditions, we were able to extract the tetrad components of the Maxwell field tensors for exterior Schwarzschild. In addition, in the presence of the geometry of the Schwarzschild solution, we found a real behaved energy density stored in electromagnetic.